2024
DOI: 10.1002/eco.2616
|View full text |Cite
|
Sign up to set email alerts
|

Fish stranding in relation to river bar morphology and baseflow magnitude: Combining field surveys and hydrodynamic–numerical modelling

Daniel S. Hayes,
Christoph Hauer,
Günther Unfer

Abstract: Hydropeaking mitigation based on down‐ramping thresholds is crucial to avoid stranding of fish and ensure sustainable hydropower production. However, the risk of stranding is influenced by several biotic and abiotic factors that interact with the ramping rate, including river morphology and baseflow magnitude. Also, at the river bar scale, the lateral or horizontal down‐ramping velocity may be of even greater importance than the vertical one as the prior integrates bar morphology. This study investigates the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(135 reference statements)
0
2
0
Order By: Relevance
“…However, their disconnection and drying out, due to down-ramping, probably trap fish in these habitats. Hayes et al (2024) observed, at the start of the downramping, that fish began to seek out deeper sections, where they remained temporarily, before no longer being able to escape when the flow receded. At low flow range, this behavior may have a strong impact on trout fry, whose preference for shallow and slow-flowing habitats makes them use habitats along the bank that are subject to stranding; grayling fry may be less affected due to their preference for higher velocities, especially during the day (Sempeski & Gaudin, 1995).…”
Section: Spatial Effects Of Morphological Microstructures Increasing ...mentioning
confidence: 97%
See 1 more Smart Citation
“…However, their disconnection and drying out, due to down-ramping, probably trap fish in these habitats. Hayes et al (2024) observed, at the start of the downramping, that fish began to seek out deeper sections, where they remained temporarily, before no longer being able to escape when the flow receded. At low flow range, this behavior may have a strong impact on trout fry, whose preference for shallow and slow-flowing habitats makes them use habitats along the bank that are subject to stranding; grayling fry may be less affected due to their preference for higher velocities, especially during the day (Sempeski & Gaudin, 1995).…”
Section: Spatial Effects Of Morphological Microstructures Increasing ...mentioning
confidence: 97%
“…Stranding may be linked to the season: when fish grow in size, they become less susceptible to being stranded (Führer et al, 2022;Hayes et al, 2024;Saltveit et al, 2001). The time of day may also be important: it has been shown that more trout fry became stranded in the day (Halleraker et al, 2003), that grayling fry tended to be more stranded at night (Hayes et al, 2024), and that cyprinid stranding preferentially occurred at night, regardless of the down-ramping rates (Führer et al, 2022). In our case, we sampled only during the day for all species.…”
Section: Spatial Effects Of Morphological Microstructures Increasing ...mentioning
confidence: 99%